2019
DOI: 10.3390/ijms20215275
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulants and Osteoporosis

Abstract: Anticoagulant agents are widely used in the treatment of thromboembolic events and in stroke prevention. Data about their effects on bone tissue are in some cases limited or inconsistent (oral anti-vitamin K agents), and in others are sufficiently strong (heparins) to suggest caution in their use in subjects at risk of osteoporosis. This review analyses the effects of this group of drugs on bone metabolism, on bone mineral density, and on fragility fractures. A literature search strategy was developed by an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 79 publications
1
41
0
9
Order By: Relevance
“…Stroke patients also have higher energy expenditure, with this interruption of energy homeostasis potentially negatively impacting the skeleton during bone remodeling (Detrembleur et al, 2003;Lee et al, 2007;Driessler and Baldock, 2010). Additionally, reduced vitamin D levels, degree of recovery, increased fall risk, and use of anticoagulants may increase bone loss post-stroke (Jørgensen et al, 2000;Smith and Carroll, 2011;Batchelor et al, 2012;Signorelli et al, 2019). Thus, increased bone screening measures are needed in stroke patients, as screening may currently be infrequent (Kapoor et al, 2019).…”
Section: Strokementioning
confidence: 99%
“…Stroke patients also have higher energy expenditure, with this interruption of energy homeostasis potentially negatively impacting the skeleton during bone remodeling (Detrembleur et al, 2003;Lee et al, 2007;Driessler and Baldock, 2010). Additionally, reduced vitamin D levels, degree of recovery, increased fall risk, and use of anticoagulants may increase bone loss post-stroke (Jørgensen et al, 2000;Smith and Carroll, 2011;Batchelor et al, 2012;Signorelli et al, 2019). Thus, increased bone screening measures are needed in stroke patients, as screening may currently be infrequent (Kapoor et al, 2019).…”
Section: Strokementioning
confidence: 99%
“…A theoretical adverse effect of heparin is osteoporosis 74 . Several in vitro and animal studies on the effects of heparin on osteogenesis showed controversial results, citing possible decreased osteoblastic or increased osteoclastic activity 74 .…”
Section: Clotting Preventionmentioning
confidence: 99%
“…A theoretical adverse effect of heparin is osteoporosis 74 . Several in vitro and animal studies on the effects of heparin on osteogenesis showed controversial results, citing possible decreased osteoblastic or increased osteoclastic activity 74 . In a crossover study of 40 patients on intermittent HD, anticoagulation was switched from UFH to low molecular weight heparin (LMWH), and biochemical markers for bone metabolism and bone densitometry were monitored longitudinally 73 .…”
Section: Clotting Preventionmentioning
confidence: 99%
“…The general pre-transplant risk factors for osteoporosis include female sex (especially post-menopause women), BMI < 23 kg/m 2 , diabetes mellitus, malnutrition, a sedentary lifestyle, smoking, excessive alcohol, vitamin D deficiency, lack of sun exposure, hypogonadism with low estrogen and progesterone levels, number of falls, end-organ failure (including cardiac, liver and renal abnormalities) and preexisting bone mineral abnormalities [ 2 ]. Long term use of unfractionated heparin (by inhibiting osteoprotegerin and enhancing osteoclastic bone resorption) and coumadin (by inhibiting gamma-carboxylation of osteocalcin) could contribute to decreases in bone density [ 16 ]. The general risk factors for osteoporosis are illustrated in Figure 2 .…”
Section: Overview Of Risk Factors In Transplant Recipientsmentioning
confidence: 99%